Kurdish broadcasting via state TV in Turkey - Cultural diversity or government's propaganda machine: The case of TRT 6 - (:unkn) unknown (INTELLECT LTD, 2018)
This article provides useful insights on the perception of TRT 6 (TRT Kurdi) by Turkey's Kurdish community regarding TV broadcast in mother tongue. The research environment of the study is Kurdish citizens who live in both south-east and west regions of Turkey. TRT 6 is a sub-channel of state TV (Turkish Radio and Television Corporation) and mainly broadcasts in the Kurmanci dialect of the Kurdish language. The results of the study show the fact that those who define themselves primarily as Kurdish - as opposed to Muslim - reject TRT 6 (and especially criticize its news coverage), and Kurds who see themselves primarily as Sunni Muslims watch it with pleasure, implying that the channel serves as a tool in 'Turkifying' the Kurds of Turkey through a common religious identity.
Keywords: Turkey; state TV; TRT; Kurdish broadcasting; ethnic minority media; Kurdish community; perception research; ETHNIC MEDIA; EUROPE